BALE-BALE DI PULAU LAE-LAE: RUANG TRADISIONAL SEBAGAI CERMINAN DINAMIKA SOSIAL DAN BUDAYA - Natsir, Ni'mah (Yayasan Nusantara Hasana Berdikari, 2024)
This research examines the role of bale-bale on Lae-Lae Island in preserving traditional values while adapting to modern social dynamics. By integrating recent field data and reviewing up-to-date literature, the study highlights how bale-bale function not only as public spaces for social interaction but also as symbols of the local community’s enduring cultural identity. Data were collected through direct observation, in-depth interviews with community leaders and local practitioners, and documentation studies that include historical archives and current publications from journals and cultural institutions. The findings are expected to provide a foundation for initiatives aimed at preserving and developing public spaces rooted in local wisdom in the modern era.